Universal Health Coverage for Inclusive and Sustainable Development : Country Summary Report for Ethiopia - Wang, Huihui (World Bank, Washington, DC, 2015)
A low-income country, Ethiopia has made impressive progress in improving health outcomes. The Inter-agency Group for Child Mortality Estimation reported that Ethiopia has achieved Millennium Development Goal (MDG) 4, three years ahead of target, with under-5 mortality at 68 per 1,000 live births in 2012. Significant challenges remain, however, with the maternal mortality ratio at 420 out of 100,000 live births. The government has introduced a three-tier public health care delivery system to deliver essential health services and ensure referral linkages, with level three as specialized hospitals (one per 3.5 million 5 million population), level two as general hospitals (one per 1 million 1.5 million), level one as primary hospitals (one per 60,000 100,000) with satellite health centers (one per 15,000 25,000) and health posts (one per 3,000 5,000). One initiative contributing greatly toward universal health coverage (UHC) is the Health Extension Program (HEP) that provides free primary care services at health posts and communities. The country is at its early stage initiating insurance schemes to provide financial protection for its citizens: Social Health Insurance (SHI) for formal sector employees and Community-Based Health Insurance (CBHI) for rural residents and informal sector employees. Public facilities are expected to provide exempted services for free, and there is a fee-waiver system for the poor.